2019
DOI: 10.33788/rcis.67.9
|View full text |Cite
|
Sign up to set email alerts
|

Difference in the Perception of Aesthetic Labour of Airlines and High-speed Rail Cabin Occupants between Industry and Academia: Discussion on Cross-Curricular Credit Programs

Abstract: This study took airlines and high-speed rail cabin occupants as subjects to explore their occupational competency profi le under the casual role enactment script. Then, the Analytic Network Process (ANP), which cross-examined the perception of aesthetic labour of those cabin occupants from the academic and industrial perspectives. The results show, fi rst, for the main criteria of the high-speed rail attendants, industry and academia both agreed that professional competencies were more important than aesthetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Industry and academia believe that aesthetic competency is more important than professional ability for flight attendants. For flight attendants, a professional attitude is the most important aesthetic competency (Yang et al , 2019). Ren (2017) reported that Chinese airlines require a higher standard of AL for women than for men; AL is gendered and context-bound.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Industry and academia believe that aesthetic competency is more important than professional ability for flight attendants. For flight attendants, a professional attitude is the most important aesthetic competency (Yang et al , 2019). Ren (2017) reported that Chinese airlines require a higher standard of AL for women than for men; AL is gendered and context-bound.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…For flight attendants, aesthetic competency is more important than professional ability (Yang et al , 2019). Therefore, a t-test was performed to examine whether the frontline employees of the airline industry had higher AL scores than their counterparts in the hotel industry.…”
Section: Methodsmentioning
confidence: 99%